Analysis of global, regional, and national burden and attributable risk factors of acute lymphoblastic leukemia and acute myeloid leukemia from 1990 to 2021 - Haojie Ni; Yun Shi; Minyan Wang; Conghua Ji (PLoS ONE, 2025)
Background Acute Leukemia (AL) is a prevalent subtype of leukemia, mainly including acute lymphoblastic leukemia (ALL) and acute myeloid leukemia (AML). The disease burden of acute leukemia has significantly shifted in recent years. The aim of this study was to evaluate global trends in the burden of disease for ALL and AML from 1990 to 2021. Methods Data on ALL and AML, encompassing incidence, mortality, disability-adjusted life-years (DALYs), and associated risk factors from 1990 to 2021, were extracted from the Global Burden of Disease (GBD) 2021 database. Estimated annual percentage changes (EAPC) were calculated to assess the changes in age-standardized incidence rate (ASIR), age-standardized mortality rate (ASMR), and age-standardized DALYs rate (ASDR). The associations between cancers burden and socio-demographic index (SDI) were also analyzed. Results Compared with 1990, the global incidence of ALL and AML in 2021 is 5.69% and 82.25% higher, respectively. During the period from 1990 to 2021, ASMR in ALL showed a large decline, while AML remained stable. The ASDR of both showed a downward trend (EAPC = −2.11% and −0.84%). Regions and countries with higher SDI also have higher rates of acute leukemia. The burden of AML is mainly distributed in the elderly population, while the burden of ALL is heavier in children. Smoking, high BMI, and occupational exposure to benzene and formaldehyde are major risk factors for AML and ALL-related deaths. Conclusion Acute leukemia remains one of the major global public health challenges, but there are different trends in different regions and countries. Acute myeloid leukemia has had a higher disease burden in recent years than acute lymphoblastic leukemia. Policy makers should develop targeted public health policies to further reduce the global burden of acute leukemia.